Case report: lymphatic malformation - Triansa, Nabila Farah; Fernando, Ego; Dewiyanti, Lilia (Institute of Computer Science (IOCS), 2024)
Lymphatic malformation is a congenital disease caused by hamartoma malformation of the lymphatic system, affecting the skin and subcutaneous tissue. Lymphangiomas typically occur before the age of 5 and are caused by improper connections of the lymphatic ducts to the main lymphatic drainage channels. A 3-day-old female patient was examined on October 13, 2023, at the NICU of Regional General Hospital K.R.M.T. Wongsonegoro (RSWN) with complaints of lumps on two parts of the body. The patient was admitted with complaints of lumps in two areas of the body, the left neck area, and the left armpit area. Laboratory results indicated decreased CRP, hypocalcemia, hyponatremia, decreased urea, decreased creatinine, anemia, decreased erythrocyte count, and hypoalbuminemia. Lymphangioma is a rare benign congenital disorder of the lymphatic system that usually presents in childhood. Lymphangiomas result from congenital or acquired abnormalities of the lymphatic system. In this patient, the lumps were on the left side of the neck and in the left axillary region. The patient was also jaundiced for 3 days after hospitalization. The patient was delivered by caesarean section due to placenta previa. At the time of additional diagnosis, the patient had neonatal pneumonia, neonatal infection, neonatal hyperbilirubinemia, hypokalemia, sepsis, moderate asphyxia, and moderate respiratory distress. Early diagnosis, intensive monitoring, and appropriate intervention for lymphatic malformations are needed to minimize the increased risk of complications. Further research is needed to evaluate the complications of lymphatic malformations and their treatment.